Fighting drugs in the Caribbean : a regional approach. - PENFOLD, P.A. (1997)
Brief review of the report by the EU team of drug experts. The team highlighted a number of gaps and weaknesses in the regional effort to combat the drugs problem, and made specific proposals on how to fill the gaps and overcome the weaknesses .